دراسة تحليلية لواقع الاستثمار الفلاحي بولاية الشلف: Analytical study of the reality of agricultural investment in the state of Chlef - وىيبة سراج; أسماء ناويس (Journal of North African Economies, 2025)
This study aims to analyze the reality of agricultural investment in the state of Chlef, through exposing the conceptual framework of agricultural investment and the most important agencies that support it. Then we go through studying the reality of agricultural investment in the state by identifying the elements and the efforts made by the relevant authorities regarding the sector and lastly we will analyze the development of plant production in the state with reference to the major problems facing the sector and the most important solutions taken in this regard. The study concluded that the state of Chlef is considered an agricultural state par excellence, as it possesses significant elements and capabilities in the agricultural aspect, as well as the ability to invest in agriculture, which qualifies it to occupy the first ranks in agricultural production, but the sector remains suffering from many problems that the competent authorities strive to find appropriate solutions for.